A Novel Fractional-Discrete-Cosine-Transform-Based Reversible Watermarking for Healthcare Information Management Systems. (23rd February 2012) - Ko, Lu-Ting; Chen, Jwu-E; Shieh, Yaw-Shih; Scalia, Massimo; Sung, Tze-Yun
Abstract : Digital watermarking is a good tool for healthcare information management systems. The well-known quantization-index-modulation- (QIM-) based watermarking has its limitations as the host image will be destroyed; however, the recovery of medical image is essential to avoid misdiagnosis. A transparent yet reversible watermarking algorithm is required for medical image applications. In this paper, we propose a fractional-discrete-cosine-transform- (FDCT-) based watermarking to exactly reconstruct the host image. Experimental results show that the FDCT-based watermarking is preferable to the QIM-based watermarking for the medical image applications.